PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS IX SMP NEGERI 6 PADANG - Putri, Rindu Widya Eka; Manda, Tysa Gustya (Departemen Matematika, 2024)
The main focus is on the importance of good academic performance for students, especially as it relates to learning mathematics at SMP Negeri 6 Padang. Currently, IX students of this school continue to have low math learning results. To solve this problem, this study applies the discovery learning model as an alternative to improve student learning outcomes. This study is quantitative using a quasi-experimental method and a non-equivalent post-test-only control group design. Data analysis shows that students learning with the discovery learning model show better learning outcomes than students using the direct learning model.Keywords– Learning outcomes, Discovery Learning,Direct Learning